Patch Size Evolution During Pulsating Aurora. Issue 6 (21st June 2019) - Partamies, Noora; Bolmgren, Karl; Heino, Erkka; Ivchenko, Nickolay; Borovsky, Joseph E.; Sundberg, Hanna
Abstract: We report both decreasing and increasing trends in the patch sizes during pulsating aurora events. About 150 pulsating auroral events over the Fennoscandian Lapland have been successfully analyzed for their average patch size, total patch area, and number of patches as a function of event time, typically 1–2 hr. An automatic routine has been developed to detect patches in the all‐sky camera images. In addition to events with decreasing and increasing average patch size evolution over the course of the pulsating aurora, events with no size trends and events with intermittently increasing and decreasing patch size trends were also found. In this study, we have analyzed a subset of events for which the average and total patch size systematically increase or decrease. The events with increasing patch size trend do not experience a decrease in the peak emission height, which was previously associated with the behavior of pulsating aurora precipitation. Furthermore, the events with increasing patch sizes have shorter lifetimes and twice as many substorm‐injected energetic electrons at geosynchronous orbit as the events with decreasing patch sizes. Half of the events with increasing patch sizes occur during substorm expansion phases, while a majority (64%) of the ones with decreasing patch sizes take place during the recovery phase. These findings suggest that the visual appearance of pulsating aurora may be used as an indication of the pulsating aurora energy deposition to the atmosphere. Key Points: Patch size in pulsating aurora has been observed to both grow and decay as a function of event time Events with growing patch sizes take place in the middle of substorms Majority of events have decaying patch size evolution, are more common, and occur toward the end of substorms